Respon Agronomi Varietas Padi terhadap Periode Kekeringan pada Sistem Sawah - Tubur, Herman Wafom; Chozin, Muhamad Achmad; Santosa, Edi; Junaedi, Ahmad (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2012)
The objective of this experiment was to identify the growth and production of rice varieties as responses to drought period in low land rice system. Rice plants were grown under plastic house in plots separated by massive walls. Drought periods were treated as main plots, i.e. water was supplied during 3, 6, and 9 weeks after rice transplanting, and control (cultivation without drought treatment). Rice varieties were used as sub plots, consisted of IR64 and Ciherang (low land improved varieties), IPB-3S (new plant type), Menthik Wangi (an aromatic local low land rice), Rokan (a hybrid rice), Way Apo Buru (amphibian type), Jatiluhur and Silugonggo (up land type). Our results showed that drought periods suppressed plant height, tiller number, spikelets length, weight of 1,000 grains, shoot dry weight and harvest index, and increased number of empty spikelets. Interaction between drought periods and rice varieties significantly affected productive tiller number, percentage of plants to flower, and grain weight per hill. Jatiluhur, Ciherang and Way Apo Buru still gave relatively high yields under drought stress indicated that those varieties were relatively tolerant to drought stress; Silugonggo and IPB-3S had medium tolerance to drought stress; IR64, Menthik Wangi and Rokan were the most sensitive varieties. Keywords: drought stress, drought tolerant, improved variety, local variety